Pengembangan UMKM di Desa Wisata Sampe Raya - Anugrah, Rifqi Arya (Politeknik Pariwisata Medan, 2024)
Development of Micro, Small and Medium Enterprises (MSMEs) This research was conducted with the aim of finding out the extent to which the development of tourist attractions has an impact on the existence of MSMEs in Sampe Raya Village. This research uses qualitative methodology, namely interview guidelines, data sources obtained from primary and secondary data. Primary data is data obtained from direct field observations, interviews with several sources who can provide information, secondary data is obtained from documentation, as well as laws and regulations related to tourist destinations, MSMEs and traditional food. The results of the research show that the development of MSMEs in Sampe Raya Village, Bukit Lawang is being developed in accordance with the potential that exists in the area, namely by improving the facilities and infrastructure to the Bukit Lawang location, so that the growth of MSMEs results in the surrounding community increasing growth. economy in Indonesia